Difficulty Analysis Factor of Online Learning Biology Subject in Grade XI MIPA - Zakiyati Salma; Rahmawati Darusyamsu (Indonesian Journal of Biology Education, 2021)
In the implementation of learning online is encountered the problem that students are experiencing learning difficulties, one of them on the subjects of Biology. Learning difficulties of students are seen from the results of learning online tend to be lower than face-to-face. The purpose of this study was to determine the factors that cause the difficulty of students to learn Biology online in grade XI MIPA SMAN 1 Kecamatan Payakumbuh. The Population and sample in this research are all students of grade XI MIPA SMAN 1 Kecamatan Payakumbuh. The research method used is the descriptive method with the instrument data collection in the form of a questionnaire. The results showed that the factor of difficulty to learn Biology online in SMAN 1 Kecamatan Payakumbuh consists of internal and external factors. Internal factors affect the 61,18% dominate by psychological (62,17%). While external factors that 65,43%, dominate by infrastructure learning online (70,79%).